Potency Analysis of the Batik MSMES Industrial in Surabaya Using Geographic Information System - Wijaya Justian; Muhammad Taufik (Institut Teknologi Sepuluh Nopember, 2019)
Behind the slowing global economic growth, MSME sector plays a very important role in maintaining the stability of national economy. In 2016 the contribution of the MSME sector reaches 60.34% for the national gross domestic product (GDP). Batik itself is a cultural heritage of the archipelago that has been recognized by the world through UNESCO as a masterpiece of humanitarian heritage for oral and nonbendawi culture (Masterpiece of The Oral and Intangible Heritage of Humanity). So in order to support and develop the sector of batik MSMEs in Surabaya required a system to monitor and analyze the potential of MSMEs in Surabaya batik is the construction of geographic information systems. The purpose of this research is to make a potential map of MSMEs of Surabaya city batik and GIS potency of batik MSME Surabaya city, which obtained by using scoring method based on distance parameter to transportation access, price range and completeness of batik product MSMEs in Surabaya. As reference and recommendation for related parties in developing potency of batik MSMEs in Surabaya. The results of the potential analysis of batik MSMEs in Surabaya are classified into 3 priority classification of high, medium, and low priority. Results of regional analysis that has MSMEs batik with high priority that is 13 MSMEs spread in South Surabaya amounted to 5 MSMEs, Central Surabaya amounted to 6 MSMEs, and North Surabaya amounted to 2 MSMEs. Then the medium priority of 24 MSMEs spread in South Surabaya amounted to 5 MSMEs, Central Surabaya amounted to 17 MSMEs, and North Surabaya amounted to 2 MSMEs. While the low priority of 4 MSMEs spread across Central Surabaya amounted to 1 MSMEs and North Surabaya amounted to 3 MSMEs